2023
DOI: 10.3389/fauot.2023.1238164
|View full text |Cite
|
Sign up to set email alerts
|

Hearing aids with tinnitus sound support reduce tinnitus severity for new and experienced hearing aid users

Abstract: ObjectiveThis interventional study tested the hypothesis that hearing aids with a tinnitus sound support feature would reduce the impact of tinnitus for both new and experienced hearing aid users over a 12-week trial period.MethodsA total of 19 experienced hearing aid users and 21 participants with no previous hearing aid experience completed the study. Hearing aids were fitted and dispensed with tinnitus masking sounds adjusted to individual preferences. The primary outcome measure was the Tinnitus Functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…The results of the current study indicate that a combination device together with counseling is effective for treatment of tinnitus. These results are in line with previous studies that investigated the effects of combination devices on tinnitus distress (Sweetow and Sabes, 2010;Herzfeld et al, 2014;Johansen et al, 2014;Stocking and Stecker, 2016;Henry et al, 2017;Tyler et al, 2017;Sanders et al, 2023). The effects of the combination device in this study are already evident after 1 month of treatment but peak at 4 months.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results of the current study indicate that a combination device together with counseling is effective for treatment of tinnitus. These results are in line with previous studies that investigated the effects of combination devices on tinnitus distress (Sweetow and Sabes, 2010;Herzfeld et al, 2014;Johansen et al, 2014;Stocking and Stecker, 2016;Henry et al, 2017;Tyler et al, 2017;Sanders et al, 2023). The effects of the combination device in this study are already evident after 1 month of treatment but peak at 4 months.…”
Section: Discussionsupporting
confidence: 93%
“…Our main inclusion criterion was the presence of bothersome tinnitus, and we did not consider hearing loss or hearing aid experience to be relevant for this exploratory study. In a recent study, Sanders et al (2023) showed that the effect of sound therapy implemented in hearing aids was comparable between new and experienced hearing aid users, hence limiting our sample to one sub-group likely would not have affected the outcome. Future investigations should look into whether the experienced benefit is different based on the degree of hearing loss or tinnitus etiology.…”
Section: Clinical Implications Study Limitations and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation